On-machine measurement and correction of machining error using laser displacement sensor - Tasuku TERAOKA; Ryuta SATO; Keiichi SHIRASE (Nihon Kikai Gakkai ronbunshu, 2018)
In order to achieve both high precision and high productivity in machining operation, machining error compensation of finished shape named as correction machining is more effective. In general, the correction machining requires additional CAD/CAM operations to generate the NC program for the correction machining, and it takes lots of time and effort. Hence, elimination of additional CAD/CAM operations for the correction machining is effective to reduce time and effort for correction machining. In this study, it is realized by integrating a newly developed On-Machine Measurement (OMM) system using a laser displacement sensor into the Digital Copy Milling (DCM) system. The DCM system was developed in our previous studies and achieves elimination of CAM operation for machining operations like a 3D printer. The OMM system can generate measurement paths automatically from a CAD model of the part based on copying principle. Tracing and measuring accuracy verified by experimental measurement of a reference sphere. Subsequently, a modified surface model represented by 3D point group data for the correction machining is generated immediately from the measurement paths and the measured machining error. Finally, the correction machining is performed immediately based on the modified surface data by the DCM system without CAM operation to generate an NC program. The effectiveness of the correction machining is validated by comparison between the finished sphere surfaces generated by the conventional and the proposed methods.